Modelling and evaluation of electrified regional aircraft propulsion systems - Zhou, Tianzhi (Cranfield University, 2023)
Electric propulsion (EP) and hybrid electric propulsion (HEP) are novel concepts that significantly impact the future aircraft design and emission reduction. These novel technologies can be used to decarbonise air transportation, especially regional aircraft in short term future. Despite the potential benefits, their implementation challenges such as durability, reliability, architectural design, subsystem health state impacts, and the dynamic behaviour of various components in an integrated propulsion system have not been fully explored. The methodologies and results in literature varied significantly, they either focused on parametrically varying technology levels for aircraft weight and range sensitivity, or considered detailed subsystem design for specific purposes. Moreover, an im- portant aspect not fully considered in most publicly available studies is to utilise fuel cell and hydrogen as the primary power supplier and energy source for future electric regional aircraft. To fill in these gaps a modular component based simulation framework is developed in this work, aiming to model and assess the design and off-design performance of integrated hybrid electric aircraft propulsion systems by capturing the characteristics, in- teractions and interdependencies of its components. The developed component models include the main devices: batteries, fuel cell system, power electronics such as converters and inverters, and electric motors. Another key feature of this simulation framework is its multi-fidelity natural. The low-fidelity models enable fast system analysis and parametric studies in various aspects for holistic mission, whereas the high-fidelity ones allow detailed subsystem sizing, architectural design and evaluation, and performance assessment. In this study, power electronics and electric motors are modelled in both low fidelity and high fidelity. For power electronics, the switching circuit elements are not included and their control mechanisms are realised by simple PI controllers for low fidelity models; whereas complete switching circuit systems are modelled to simulate their power losses and control logic for high fidelity models. For electric motor systems, dq model with PI control system are used as low fidelity models whereas a MotorCAD based PMSM performance map, with ‘Id = 0’ control strategy and SVPWM modulation inverter circuit are used as high fidelity models. The simulation framework was applied to study a 50 PAX, ATR42 like regional aircraft. Two forms of propulsion architectures were investigated: a pure PEMFC powertrain and a hybrid electric one. Based on the developed electric models and simulation framework, various cases and scenarios not studied in literature were investigated. For pure PEMFC system, the impacts of air mass flow rate and air supply pressure variation on fuel cell based system performance were investigated; The degradation impacts of fuel cell and battery on the system performance and sizing were also studied; A thorough discussion on fuel cell multi-stack architectural design was presented. Whereas for hybrid electric system, a comparative study between hybrid battery, hybrid fuel cell and hybrid battery/fuel cell propulsion system was conducted. The study evaluated key factors that can affect the electric system weight, such as mission length, hybridisation level, battery cycling number, etc. All these problems are significant and need to be solved before implementing the novel electrical propulsion technologies on regional aircraft. Key findings and important conclusions were drawn from these case studies. For pure PEMFC system, it was found that the FC system normally exhibited higher efficiency at low power level (e.g. approximately 45% at top of climbing and 58% during descent). Therefore, a slight over-sized FC system can help improve the efficiency performance; Secondly, the effects of FC air supply pressure and mass flow rate on FC system efficiency and robustness were investigated. It was found that, although there was reduction in FC stack efficiency when keeping a relatively low FC air supply pressure, the overall FC system efficiency was improved throughout flight mission. Also, a potential risk of low air supply rate was identified and a control strategy balancing efficiency and system reliability was proposed; Thirdly, FC degradation can cause imbalance performance of the whole multi-stack FC system. In this study, a 10% voltage and current degradation from a single FC was used, and it was found that such single cell level degradation can cause the whole FC system malfunction for some flight phases, which was detrimental. A detailed solution to avoid the malfunctioning risk was discussed in this study. For hybrid electric system, it was found that, under current and short-term technology level, FC based hybrid propulsion system generally had weight advantages over battery based one for regional aircraft. Specifically, a case study demonstrated that pack-level battery S.E. was expected to reach around 335-, 406-, and 543 Wh/kg to compete against the hybrid fuel cell system for 200-, 300-, and 600 nmi mission for the same power profiles. This required huge technology improvement for battery, since its cell level state-of-art S.E. was merely 250 Wh/kg when the research was initiated. Moreover, when battery cycling degradation was considered, further battery technology improvement was required.
Keywords: Architecture; CHARM; Degradation; Electric Propulsion; Electrical System Simulation; Hybrid Electric Propulsion; Hydrogen; Multi-fidelity Modelling; PEMFC; Regional Aircraft